Training and Career Development on Employee Productivity at New Book Store in Malang Regency - Yohanes Kalvin Jemarut; Cakti Indra Gunawan; Fendiyatmi Kusufa (International Research & Development for Human Beings (IRDH), 2026)
This study aims to determine and analyze the influence of transformational leadership, training, and career development on employee productivity at the New Book Store in Malang Regency. Employee productivity is an important factor in improving company performance, so it requires leadership that is able to motivate, as well as training and career development programs that can improve employee abilities and competencies. This study uses a quantitative approach with a survey method by distributing questionnaires to employees as respondents. The data analysis technique used is multiple linear regression analysis to determine the partial and simultaneous effects between independent variables on the dependent variable. The results of the study indicate that transformational leadership, training, and career development have a positive and significant effect on employee productivity both partially and simultaneously. The most dominant variable affecting employee productivity is training, because it can directly improve employee skills, knowledge, and work abilities. This study concludes that increasing employee productivity can be achieved through the implementation of effective transformational leadership and the implementation of continuous training and career development programs. The results of the study are expected to be a consideration for companies in formulating human resource management policies to improve employee productivity.